2015
DOI: 10.1097/ccm.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Patients Who Present to the Emergency Department With Sepsis and Progress to Septic Shock Between 4 and 48 Hours of Emergency Department Arrival*

Abstract: Approximately 12% of septic emergency department patients develop shock within 48 hours of presentation, and more than half of these patients develop shock after the first 4 hours of emergency department arrival. Over a third of patients who have sepsis within 4 hours of emergency department arrival and develop septic shock between 4 and 48 hours of emergency department arrival are not admitted to an ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 17 publications
4
33
1
Order By: Relevance
“…We found that for each hour that passed between ED triage and antimicrobial administration, the risk of progression to septic shock increased by 8.0%, highlighting the importance of early identification and treatment of patients with infection-induced organ dysfunction. The percentage of patients progressing to septic shock in our study was slightly higher than previously reported (6,7,8, 14,15). This is likely because we did not include patients with sepsis, defined as infection + SIRS (ICD-9 diagnosis code 995.91), and because our patients required the presence of an ICD-9 diagnosis code for severe sepsis or septic shock.…”
Section: Discussioncontrasting
confidence: 89%
“…We found that for each hour that passed between ED triage and antimicrobial administration, the risk of progression to septic shock increased by 8.0%, highlighting the importance of early identification and treatment of patients with infection-induced organ dysfunction. The percentage of patients progressing to septic shock in our study was slightly higher than previously reported (6,7,8, 14,15). This is likely because we did not include patients with sepsis, defined as infection + SIRS (ICD-9 diagnosis code 995.91), and because our patients required the presence of an ICD-9 diagnosis code for severe sepsis or septic shock.…”
Section: Discussioncontrasting
confidence: 89%
“…A 48-h window was selected based on prior studies have found that significant progression and potential decompensation of septic patients in the ED typically occurs by this point [11, 12]. Patients were classified as “needing early escalation” if admitted to a non-ICU level of care from the ED but subsequently upgraded to ICU level within the first 48 h or if they died in the wards within 48 h of admission.…”
Section: Methodsmentioning
confidence: 99%
“…The following 8 variables were considered in the forward selection model-building process: serum lactate ≥4 mmol/L, presence of pneumonia, time to antibiotic administration, nighttime admission, Charlson co-morbidity index, shock index, quantity of fluid administered, and age. These variables were selected based upon prior studies that have shown that these are risk factors for unexpected ICU transfer, significant biological plausibility, or significant findings in the univariate analysis [1012, 14]. A separate multivariable logistic model was used to determine if unexpected ICU transfer was an independent risk factor for death and included the following four variables: serum lactate ≥4 mmol/L, time to antibiotic administration, volume of fluids resuscitation, and shock index.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant proportion (~18%) of ED patients develops shock within the first 72 hours of admission, although many give scant clinical indication of this impending event during the initial 3–4 hours of their evaluation, making it difficult to risk-stratify these patients 4–6. In one study, one-third of patients presenting to the ED with sepsis who developed septic shock during the first 2 days of hospitalisation were not initially admitted to an ICU 6. Importantly, unplanned transfer to a critical care unit following initial admission to a medical ward has been associated with poorer outcomes 7 8…”
Section: Introductionmentioning
confidence: 99%